Disparities in CD4+ T-Lymphocyte Monitoring Among Human Immunodeficiency Virus-Positive Medicaid Beneficiaries: Evidence of Differential Treatment at the Point of Care. (5th July 2014) - Davis, Anna C.; Watson, Greg; Pourat, Nadereh; Kominski, Gerald F.; Roby, Dylan H.
Abstract : This study identifies substantial disparities in receipt of guideline-concordant CD4 tests among HIV-positive Medicaid beneficiaries despite evidenced access to health care. Failure to provide CD4 tests is critical because of their role in determining appropriateness of antiretroviral treatment. Abstract: Background.  Monitoring of immune function, measured by CD4 + T-lymphocyte (CD4) cell count, is an essential service for people with human immunodeficiency virus (HIV). Prescription of antiretroviral (ARV) medications is contingent on CD4 cell count; patients without regular CD4 monitoring are unlikely to receive ARVs when indicated. This study assesses disparities in CD4 monitoring among HIV-positive Medicaid beneficiaries. Methods.  In this retrospective observational study, we examined 24 months of administrative data on 2250 HIV-positive, continuously enrolled, fee-for-service, Medicaid beneficiaries with at least 2 outpatient healthcare encounters. We used logistic regression to evaluate the association of patient demographics (age, gender, race or ethnicity, and language) with receipt of at least 1 CD4 test per year, controlling for other potentially confounding variables. Results.  Having a history of ARV therapy was positively associated with receipt of CD4 tests. We found racial or ethnic, gender, and age disparities in CD4 testing. Among individuals with a history of ARV use, all racial or ethnic groups were significantly less likely to have CD4 tests than White non-Latinos (African Americans, odds ratio [OR] = 0.35, P < .0001; Asian or Pacific Islanders, OR = 0.31, P = .0047; and Latinos, OR = 0.42, P < .0001). Conclusions.  We identified disparities in receipt of CD4 tests, a finding that may elucidate one potential pathway for previously reported disparities in ARV treatment. Further qualitative and quantitative research is needed to identify the specific factors that account for these disparities, so that appropriate interventions can be implemented.